Teachers’ contributions to the school climate and using empathy at work: implications from qualitative research in two European countries - Martinsone, Baiba; Žydžiūnaite, Vilma (Frontiers in Psychology, 2023)
This research aimed to reveal the factors that, based on their experiences, teachers consider important in their contribution to a positive school climate and in their relationship with students when it comes to using empathy. Teachers from two European countries—Latvia (n = 83) and Lithuania (n = 69)—participated in the research. Data were collected through focus group-based interviews and analyzed using latent qualitative content analysis. The results revealed the teachers’ shared understanding of the importance of communication and professional development. However, only Lithuanian teachers emphasized strengthening institutional values and other more collectivistic aspects; the answers of Latvian teachers were specific and suggested more of an individualistic attitude, like allocating personal responsibility to use appropriate instructional strategies. This study draws attention to contextual and cultural factors of teachers’ work and actualizes their educational needs.